Enhancing productivity of wheat-maize cropping sequence on a sandy loam soil - GUPTA, SANJEEV KUMAR; GHOSH, MAINAK; GUPTA, REENA; SINGH, K. K.; DUBEY, S. N.; SINGH, T. P (Journal of Soil and Water Conservation, 2020)
Sandy soils having low organic matter and low N content often result in low crop yields. There are socioeconomic constraints in adoption of balanced application of chemical fertilizers. Using biofertilizers can be a cheap alternative to fertilizer nitrogen. The present investigation was carried out on N management and biofertilizer application in wheat-maize cropping sequence during the year 2005-2006 and 2006-2007 in the research farm of Lakhaoti, western India to study the effect of biofertilizers and nitrogen on yield and N-use efficiency in wheat and maize on a sandy loam soil. Seed inoculation with biofertilizers significantly increased wheat plant height over control during both the years of study. However, no significant residual effects of biofertilizer inoculation were observed in terms of the maize plant height. Application of fertilizer nitrogen @ 60 and 120 kg ha-1produced taller plants of both wheat and maize in comparison to control during both the seasons of study. LAI of the maize crop increased significantly with application of fertilizer nitrogen @ 60 as well as 120 kg ha-1 in comparison to control. Seed inoculation with Rhizobacteria and Azotobacter significantly increased the grain yield of wheat by 5.96 and 7.55%, respectively, over control. Nitrogen application @ 120 kg/ha enhanced grain yield, Agronomic N-use efficiency and N recovery efficiency in Wheat, however, the differences between 60 and 120 kg N/ha were not significant. Rhizobacteria and Azotobacter inoculation increased the straw yield by 9.23% and 7.27%, respectively over no inoculation. Nitrogen application up to 60 kg ha-1 significantly increased the straw yield of wheat over control during both the years. The stover yield of maize was significantly increased with each increase in direct applied N up to 120 kg/ha in both the years.